CURRENT STATE OF THE PROBLEM OF INCREASE QUALIFICATIONS OF TEACHERS PHYSICAL EDUCATION - V.Ye. Andrivnov; V.I. Marchyk; T.V. Andrianov (Academy of Cognitive and Natural Sciences, 2022)
The article is devoted to the modern problems of increasing qualification of physical training teacher.